The Role of Competitive Intelligence In Shaping Australia's Defence Strategy To Mitigate China's Influence In The Indo-Pacific Region - Tony Probo Gurihastyo; Muhammad Syaroni Rofli; Heru Subiyantoro (Asian Journal of Social and Humanities, 2024)
China's significant economic development and military modernization in the last few decades has resulted in a change in the global geopolitical situation in the Indo Pacific Region. China is increasingly aggressive in spreading its influence and one of the steps taken by China is the Belt and Road Initiative (BRI) project. In carrying out BRI through maritime routes, China has made the South China Sea the main route. On the basis of the Nine-Dashed Line, China is aggressively asserting its control claims in the South China Sea. This made the situation in the South China Sea heat up due to protests from several countries. As one of the countries in the Indo Pacific Region, Australia, by using a competitive intelligence mechanism, views what China has done as a threat to its national security, as written in the National Defense: Defense Strategic Review 2023 report. Therefore, Australia must create a defense strategy to mitigate this threat. The author conducted this research using qualitative methods by collecting data from observation, document study, and literature study. This study aims to determine the role of competitive intelligence in the framework of forming a defense strategy carried out by Australia as a mitigation measure against China's defense advances and China's influence spread in the Indo Pacific Region.